Rare earth elements behaviour at west coast of Peninsular Malaysia rocky shore ecosystem using saccostrea cucullata as bioindicator - Yunus, Kamaruzzaman; Miskon, Mohd Fuad; Faudzi, Fikriah; Rahman, Md. Mokhlesur; Chuan, Ong Meng; Shaari, Hasrizal (Chemical Publishing Co., 2017)
This study focuses on the assessment of rare earth elements (REEs) in rocky shore ecosystem along west coast region of Peninsular Malaysia coastal waters, describing their partitioning in selected body part of Saccostrea cucullata and deliberating on interspatial variability. Samples were digested using Teflon Bomb technique and concentrations of 14 naturally occurring REEs were measured using ICP-MS technique, along with selected trace metals for additional data. The REEs fractionation patterns normalized to chondrite were remarkably similar, indicating a common source of the REEs. Consistent REEs abundance patterns were found in all samples, with enrichment of LREE over HREE, which implies that REEs are transported as a coherent group through west coast of Peninsular Malaysia aquatic ecosystems. Quantification of anomalies calculated using values normalized to chondrite data presented ratios higher than unity for Ce and ratios lower than unity for Eu in all sites. Filter feeder S. cucullata is considered to be highly potential as a bioindicator for REEs, undoubtedly due to its feeding behaviour that is much related to suspended particles as REEs sources. Comparative results showed that the values are considerably below the safety limit, with the exception of Ce and Nd in the soft tissue of S. cucullata.